Modelling travellers' behaviour in a route choice experiment with information under uncertainty: calibration, validation, and further refinements. Issue 3 (16th March 2023) - Di Pace, Roberta; Bruno, Francesca; Bifulco, Gennaro N.; de Luca, Stefano
ABSTRACT: Several systems have been proposed in recent years for Advanced Traveler Information Systems (ATIS), ranging from personal (mobile application, on-board) navigation to VMS (Variable Message Signs). All these applications are essentially aimed at assisting the travelers in their travel choices by means of technologically dispatched information about traffic network structure and traffic conditions. It is well known that in ATIS applications one of the key issues to be addressed concerns the accuracy of the dispatched information, here intended as the ability of the system in supplying information that can be verified by the travelers to be correct (affected by a small error). This paper aims at proposing some analytical models able to simulate the effects of the (in)accuracy on travelers' compliance with information.